Postoperative assessment of dental implants by using multi-slice computed tomography - Resha J Al-Sudani; Lamia H Al-Nakib; Shifaa H Al-Naimi (College of Dentistry/ University of Baghdad, 2013)
Background: Implantology is a fast growing area in dentistry. One of the most common issues encountered in dental implantation procedures is the lack of adequate preoperative planning. Conventional radiography may not be able to assess the true regional three-dimensional anatomical presentation. Multi Slice Computed Tomography provides data in 3-dimentional format offering information on craniofacial anatomy for diagnosis; this technology enables the virtual placement of implant in a 3-Dimensional model of the patient jaw (dental planning). Patients, Material and Methods: The sample consisted of (72) Iraqi patients indicated for dental implant (34 male and 38 female), age range between (20-70) years old. They were examined during a time period started from December 2012 to April 2013. All the patients who subjected to implant treatment depending on the pre-operative panoramic radiograph were referred Al-Kharkh General hospital, spiral CT scan Department, for postsurgical assessment evaluate the angulation of fixture in relation to the angulation of bone in coronal and sagittal sections by using Multi-Detector Computed Tomography. Results: The present study showed that the angulation of implant affected by age, sector, and tooth position in the same jaw, and not affected by gender. Conclusion: Multi-Slice Computed Tomography provides a great understanding about bone angulation, it necessary as a diagnostic tool for treatment planning pre and post-operatively.